Bending oxygen saturation index and risk of worsening heart failure events in chronic heart failure. (29th August 2022) - de la Espriella, Rafael; Amiguet, Martina; Miñana, Gema; Rodríguez, Juan Carlos; Moyano, Patricia; Segarra, Daniel; Fernández, Julio; Santas, Enrique; Núñez, Gonzalo; Lorenzo, Miguel; Bonanad, Clara; Alania, Edgardo; et al.
ABSTRACT: Aims: Bendopnea is a clinical symptom of advanced heart failure with uncertain prognostic value. We aimed to evaluate whether bendopnea and the change in oxygen saturation when bending forward (bending oxygen saturation index [BOSI]) are associated with adverse outcomes in ambulatory chronic heart failure (CHF) patients. Methods and results: We prospectively evaluated 440 subjects with symptomatic CHF. BOSI was defined as the difference between sitting and bending oxygen saturation (SpO2 ). The endpoint was the total number of worsening heart failure (WHF) events (heart failure hospitalization or urgent heart failure visit requiring parenteral diuretic therapy). The mean age was 74 ± 10 years, 257 (58.6%) were male, and 226 (51.4%) had a left ventricular ejection fraction <50%. Bendopnea was present in 94 (21.4%) patients, and 120 (27.3%) patients had a BOSI ≥−3%. The agreement between BOSI ≥−3% and bendopnea was moderate (Gwet's AC 0.482, p < 0.001). At a median (p25%–p75%) follow‐up of 2.17 years (0.88–3.16), we registered 441 WHF events in 148 patients. After multivariable adjustment, BOSI was independently associated with the risk for total WHF episodes (overall, p < 0.001). Compared to improvement/no change in SpO2 when bending (BOSI 0%), those with BOSI ≥−3% showed an increased risk of WHF events (incidence rate ratio [IRR] 2.16, 95% confidence interval [CI] 1.67–2.79; p < 0.001). In contrast, bendopnea was not associated with the risk of total WHF episodes (IRR 1.04, 95% CI 0.83–1.31; p = 0.705). Conclusions: In ambulatory and stable CHF patients, BOSI ≥−3% and not bendopnea was independently associated with an increased risk of total (first and recurrent) WHF episodes. Awareness of SpO2 while assessing bendopnea may be a useful tool for predicting heart failure decompensations. Abstract : Association between BOSI and the risk of future WHF events (first and recurrent). BOSI, bending oxygen saturation index; HF, heart failure; IRR, incidence rate ratio; SpO2, oxygen saturation; WHF, worsening heart failure.